Bioengineering for head and neck reconstruction: the role of customized flaps. Issue 2 (April 2021) - Gualtieri, Tommaso; Taboni, Stefano; Ferrari, Marco; Gilbert, Ralph
Abstract : Purpose of review: The purpose of this review is to provide the reader with an overview of the present and future applications of bioengineering for head and neck reconstruction, ranging from the application of Computed Assisted Surgery (CAS) to the most recent advances in 3D printing and tissue engineering. Recent findings: The use of CAS in head and neck reconstruction has been demonstrated to provide shorter surgical times, improved reconstructive accuracy of bone reconstruction, and achieves better alignment of bone segments in osteotomized reconstructions. Beyond its classical application in bone reconstructions, CAS has demonstrated reliability in the planning and harvesting of soft tissue flaps. To date, literature regarding bioengineering for head and neck reconstruction is mainly focused on in-vitro and animal model experiments; however, some pioneering reports on human patients suggest the potential feasibility of this technology. Summary: Bioengineering is anticipated to play a key role in the future development of customized flaps for head and neck reconstruction. These technologies are particularly appealing as a new technology to address certain unsolved challenges in head and neck reconstruction.